Diagnosis and Surgical Treatment of a Gunshot Fragment Wound of the Heart with a Threat of Coronary Artery Perforation - Kostiantyn V. Humeniuk; Oleksandr V. Kupchynskyi; Vasyl V. Fylypchuk; Maryna M. Serdiuk; Volodymyr O. Kupchynskyi; Artem M. Petlytskyi; Rostyslav M. Vitovskyi; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2023)
Each case of fragment heart damage is unique and requires careful preparation for surgical intervention. Complexity of such operations is explained by the probability of unwanted complications associated with technical measures and aimed at extracting fragments of the most diverse localization.The aim. To demonstrate the possibilities of effective diagnosis and optimal surgical treatment of a gunshot fragment wound of the heart with the threat of coronary artery perforation.Material and methods. The article presents a case of diagnosis and surgical treatment of a fragment heart damage with intramyocardial damage of the left ventricular wall with localization under the circumflex branch of the left coronary artery with the threat of its perforation. One day has passed since a mine blast injury. Diagnosis was based on the use of contrast enhanced computed tomography (CT) and coronary angiography.Results. During the diagnostic process, the need to use a CT scan with mandatory contrast media arose, which made it possible to confirm the presence of a fragment in the immediate vicinity of the coronary artery. Coronarography provided additional information which revealed contact of the fragment with the coronary artery with the threat of its perforation. Immediate surgery with artificial blood circulation with stepwise application of magnets of increasing power allowed safe removal of the fragment, avoiding damage to the coronary artery.Conclusions. The most accurate topical diagnosis of fragment localization in heart damage requires CT diagnosis with mandatory contrast media and, if possible, with 3D reconstruction, which allows for surgical intervention with a minimal risk of intraoperative complications. Location of the fragments near the coronary vessels may threaten their damaging during removal and requires careful manipulation to prevent injury to the heart vessels. Detection and removal of sharp fragments located near the coronary vessels require stepwise application of magnets of increasing power to bring the fragment to a safe zone with its subsequent extraction.